Blood-Brain Barrier Disruption by Lipopolysaccharide and Sepsis-Associated Encephalopathy - Peng, Xiaoyao; Luo, Zhixuan; He, Shuang; Zhang, Luhua; Li, Ying (Frontiers in Cellular and Infection Microbiology, 2021)
As a complex multicellular structure of the vascular system at the central nervous system (CNS), the blood-brain barrier (BBB) separates the CNS from the system circulation and regulates the influx and efflux of substances to maintain the steady-state environment of the CNS. Lipopolysaccharide (LPS), the cell wall component of Gram-negative bacteria, can damage the barrier function of BBB and further promote the occurrence and development of sepsis-associated encephalopathy (SAE). Here, we conduct a literature review of the direct and indirect damage mechanisms of LPS to BBB and the relationship between these processes and SAE. We believe that after LPS destroys BBB, a large number of inflammatory factors and neurotoxins will enter and damage the brain tissue, which will activate brain immune cells to mediate inflammatory response and in turn further destroys BBB. This vicious circle will ultimately lead to the progression of SAE. Finally, we present a succinct overview of the treatment of SAE by restoring the BBB barrier function and summarize novel opportunities in controlling the progression of SAE by targeting the BBB.